The Potential of Calcium Phosphate Nanoparticles as Adjuvants and Vaccine Delivery Vehicles - Sun, Zhe; Li, Wenyi; Lenzo, Jason C.; Holden, James A.; McCullough, Michael J.; O’Connor, Andrea J.; O’Brien-Simpson, Neil M. (Frontiers in Materials, 2021)
Vaccination is one of the most efficacious and cost-effective ways to protect people from infectious diseases and potentially cancer. The shift in vaccine design from disrupted whole pathogens to subunit antigens has brought attention on to vaccine delivery materials. For the last two decades, nanotechnology-based vaccines have attracted considerable attention as delivery vehicles and adjuvants to enhance immunogenicity, exemplified with the current COVID vaccines. The nanoparticle vaccines display unique features in protecting antigens from degradation, controlled antigen release and longer persisting immune response. Due to their size, shape and surface charge, they can be outstanding adjuvants to achieve various immunological effects. With the safety and biodegradable benefit of calcium phosphate nanoparticles (CaP NPs), they are an efficient carrier for vaccine design and adjuvants. Several research groups have studied CaP NPs in the field of vaccination with great advances. Although there are several reports on the overview of CaP NPs, they are limited to the application in biomedicine, drug delivery, bone regeneration and the methodologies of CaP NPs synthesis. Hence, we summarised the basic properties of CaP NPs and the recent vaccine development of CaP NPs in this review.